Experiencing international business and management - Punnett, Betty Jane. (Belmont, Calif. : Wadsworth, 1994)
This book is divided into three parts: Exercises; Projects; and Profiles and Mini-Cases.
Keywords: Management; Business enterprises; International business enterprises -- Management -- Simulation methods